Rotavirus vaccine effectiveness and impact in Uzbekistan, the first country to introduce in central Asia. Issue 2 (1st February 2021) - Eraliev, Umid; Latipov, Renat; Tursunova, Dilorom; Wasley, Annemarie; Daniels, Danni; Ismoilov, Umed; Akramova, Manzura; Sultanova, Mehri; Yuldashova, Dilbar; Barakaev, Bahodir; Mutalova, Vazira; Tuychiev, Laziz; et al.
ABSTRACT: Uzbekistan, the most populous country in central Asia, was the first in the region to introduce rotavirus vaccine into its national immunization program. Rotarix (GlaxoSmithKline Biologicals, RV1) was introduced in June 2014, with doses recommended at age 2 and 3 months. To evaluate vaccine impact, active surveillance for rotavirus diarrhea was reestablished in 2014 at 2 hospitals in Tashkent and Bukhara which had also performed surveillance during the pre-vaccine period 2005−2009. Children aged <5 y admitted with acute diarrhea had stool specimens collected and tested for rotavirus by enzyme immunoassay. Proportions testing rotavirus-positive in post-vaccine years were compared with the pre-vaccine period. Vaccine records were obtained and effectiveness of 2 RV1 doses vs 0 doses was estimated using rotavirus-case and test-negative design among children enrolled from Bukhara city. In 2015 and 2016, 8%−15% of infants and 10%−16% of children aged<5 y hospitalized with acute diarrhea at the sites tested rotavirus-positive, compared with 26% of infants and 27% of children aged<5 y in pre-vaccine period (reductions in proportion positive of 42%−68%, p <.001). Vaccine effectiveness of 2 RV1 doses vs 0 doses in protecting against hospitalization for rotavirus disease among those aged ≥6 months was 51% (95% CI 2–75) and is based on cases predominantly of genotype G2P[4]. Vaccine effectiveness point estimates tended to be higher against cases with higher illness severity (e.g., clinical severity based on modified Vesikari score ≥11). Our data demonstrate that the monovalent rotavirus vaccine is effective in reducing the likelihood of hospitalization for rotavirus disease in young children in Uzbekistan.